Jellyfish degradation in a shallow coastal Mediterranean lagoon - Marques, Raquel (2021)
Recurrent jellyfish blooms in the coastal zone call for understanding the impacts of jelly-falls on the functioning of benthic communities, especially in shallow enclosed ecosystems where their biomass can affect local carbon cycling and productivity. Each year, blooms of the jellyfish Aurelia coerulea appear and collapse in a semienclosed coastal Mediterranean lagoon (the Thau lagoon, south of France). Although the lagoon is shallow, large accumulations of dead jellyfish are never observed on its bottom, so it was hypothesized that decaying jellyfish were rapidly consumed by local macrobenthic organisms. The current work aimed to test this hypothesis, by estimating the impact of the presence of dead A. aurelia medusae on local macrobenthic community composition and assessing their biomass loss rates under different scenarios of accessibility by the macrobenthos. Unexpectedly, our results revealed a limited role of macrobenthic scavengers in the disappearance of dead medusae, although this later was particularly fast (19-78h). Only one taxon (Tritia sp., Nassariidae family) showed a significant response to the presence of dead A. coerulea medusae on the seabed. Thus, our results suggest that the fast disappearance of dead jellyfish biomass in Thau results from its rapid degradation and consumption by local microorganisms, likely due to the combined effects of high local temperatures and the small size of A. coerulea medusae. Thus, the important biomass produced during A. aurelia blooms in Thau might essentially boost its microbial food web. The potential role of jellyfish blooms in controlling biogeochemical cycles and food web functioning in shallow lagoons is discussed, underlying the need to include this process in ecosystem-based models.